Formation of reactive species via high power microwave induced DNA damage and promoted intrinsic pathway-mediated apoptosis in lung cancer cells: An in vitro investigation - Juie Nahushkumar Rana; Sohail Mumtaz; Ihn Han; Eun Ha Choi (Fundamental Research)
Lung cancer continues to be the second most common cancer diagnosed and the main cause of cancer-related death globally, which requires novel and effective treatment strategies. When considering treatment options, non-small cell lung cancer (NSCLC) remained a challenge, seeking new therapeutic strategies. High-power microwave (HPM) progressions have facilitated the advancement of new technologies as well as improvements to those already in use. The impact of HPM on NSCLC has not been investigated before. In this work, we uncovered the effect of pulsed HPM on NSCLC (H460 and A549) for the first time and the most likely underlying mechanisms. Two NSCLC (H460 and A549) cells and lung normal MRC5 were exposed to HPM (15, 30, 45, and 60) pulses (2.1 mJ/pulse). After exposure, the effects were observed at 12, 24, 48, and 72 h. HPM primarily increases the level of intracellular reactive species by a strong electric field of ∼27 kV/cm, which altered NSCLC viability, mitochondrial activity, and death rates. A model for the production of intracellular reactive species by HPM was also presented. NSCLC is found to be affected by HPM through DNA damage (upregulation of ATR/ATM, Chk1/Chk2, and P53) and increased expression of apoptotic markers. NAC scavenger and CPTIO-inhibitor confirm that the reactive species are mainly accountable for cellular effects. In order to ensure suitability for real-world usage, the skin depth was calculated as 30 mm. ROS played a main role in inducing cellular effects, with NO species possibly playing a contributing role. These findings clarify the cellular mechanisms underlying HPM-induced cell death, potentially advancing therapeutic approaches for treating NSCLC, and a useful first step for future investigations in this area. Moreover, this technique has the potential to serve as an adjunct to non-surgical methods in cancer therapy.